Trends and disparities in dilated cardiomyopathy related mortality among adults in the United States: A CDC WONDER analysis (1999–2023) - Zian Zafar Cheema; Mohammad Atout; Taha Kassim Dohadwala; Ahmed Talaat Deiab; Aya Abouayana; Hazim Mesmar; Asmaa Hasan; Amaad Alam Shah; Muhammad Babar Mahmood; Daniel James Lewis; Hasan Ahmed; Maryam Shahzad; et al. (PLoS ONE, 2025)
Background Dilated cardiomyopathy (DCM) is a progressive myocardial disease characterized by ventricular dilation and impaired systolic function, often leading to heart failure and increased mortality. This study aims to analyze DCM-related mortality trends among adults in the United States from 1999 to 2023. Methods Trends in DCM-related mortality among adults aged ≥ 25 years from 1999 to 2023 were analyzed using the CDC WONDER multiple-cause of death database. Age adjusted mortality rates (AAMRs) per 100,000 persons and annual percent change (APC) were calculated and stratified by year, sex, race, census region and urbanization status. Results From 1999 to 2023, there were 184,073 deaths in the United States attributed to DCM. Over this period, the AAMR declined from 5.19 in 1999 to 2.34 in 2023. Between 1999 and 2002, the AAMR decreased significantly from 5.19 to 4.38 (APC −6.20* [95% CI, −12.42 to −0.72; P = 0.0208]). The trend remained stable between 2002 and 2005, followed by a significant decline between 2005 and 2014, where the AAMR decreased from 4.96 to 2.66 (APC −6.84* [95% CI, −9.00 to −3.05; P = 0.0300]). The trend then remained relatively unchanged from 2014 to 2023. In 2023, males (3.4) averaged a considerably higher AAMR than females (1.38). Among racial groups, the highest AAMR in 2023 was reported in the Non-Hispanic (NH) Black group (3.77), followed by the NH White group (2.3), the Hispanics and Latinos (1.67) and the NH Others group (NH Asians and NH Native American Indian or Alaskan Native) at 1.23. Overall from 1999 to 2020, rural areas (3.52) averaged a significantly higher AAMR than urban areas (3.50). Regionally, in 2023, the Western region averaged the highest AAMR at 2.69, followed by the South at 2.31, the Midwest at 2.42 and lastly the Northeast at 1.83. Conclusion Our analysis revealed a significant decline in DCM-related mortality rates in the United States from 1999 to 2023, with the most substantial reductions occurring between 1999 and 2014. However, disparities persist, with higher mortality rates observed in males, NH Black individuals, and rural populations. Regional variations also highlight the need for targeted interventions to further reduce the burden of DCM.